Study of decalcified bone samples by dielectric dissipation factor - Ireta Moreno, F; Martínez Celorio, R A; Gonzalez Rolón, B; Morales Sánchez, E; Castro Sánchez, R; Hernández Fusilier, D; González Peña, R; Salvador Palmer, R (Revista Mexicana de Ingenieria Biomedica, 2018)
In this paper, it is introduced a method to determine the bone decalcification using the so called dielectric dissipation factor (DDF). This study was developed using a set of eight samples taken from hog bone. These samples were arranged in a tablet shape. These tablets were prepared following a protocol that provokes a controlled decalcification degree. The samples were tested in a capacitive cell that was interconnected with an electric impedance analyzer. This equipment is able to measure the DDF as a function of frequency. The aforementioned tests were run in the interval of 70 MHz to 90 MHz. These results suggest that the proposed technique is a good choice to evaluate the bone decalcification quantitatively. The importance of this study is the possibility of develop a non invasive technique to measure the decalcification degree. Indeed, this method may be used to design a new generation of equipments that can be used to measure the osteoporosis. A non invasive method offers a less dangerous procedure to determine the effect of this illness, especially because the available schemes use ionizing radiation.